1992
DOI: 10.22260/isarc1992/0085
|View full text |Cite
|
Sign up to set email alerts
|

Development of Discharged Soil Measuring Device for Shield Tunneling Machines

Abstract: It is very important to know the volume of discharged soil for more adequate excavating control of the shield tunneling machines . In confined soil shields and mechanical shields, excavated soil is discharged by belt conveyors and muck cars, so it has been difficult to evaluate the discharged soil volume . In this study we have developed a discharged soil, measuring system to evaluate the volume of discharged soil in real time . This system is equipped with ( 1) an ultrasonic sensor or (2) light section micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At present, significant advancements have been achieved in the research and development of shield tunneling machines by scientists and engineers around the world. For example, Huo et al [1] and Li et al [2] analyzed the mechanical properties of the cutterhead of the shield machine, and optimized the cutterhead to significantly reduce the equivalent stress and deformation of the cutterhead; Shi et al [3] analyzed the torque of cutterhead of the EPB shield machine, and found that the cutter opening and earth pressure are two important factors affecting torque of the cutter; Qi et al [4] studied the rock breaking process of the cutter of the road header, and determined the optimal knife spacing of the rock; Moeinossadat et al [5] , Zhu、Li [6] and Li et al [7] studied the surface subsidence caused by shield tunneling, and proposed effective methods for predicting surface settlement; Ooishi et al [8] developed a shield bulldozer measuring device to facilitate accurate measurement of the discharged muck; Shi et al [9][10] and Yang et al [11] analyzed the energy conservation of the shield machine system to reduce the energy loss of the shield machine; Yang et al [12][13] ,Wang et al [14][15] , Zhang et al [16] and Zhao et al [17] studied the dynamics of the shield thruster system which is helpful for the in-depth study of the dynamic characteristics of the shield thrust system;…”
Section: Introductionmentioning
confidence: 99%
“…At present, significant advancements have been achieved in the research and development of shield tunneling machines by scientists and engineers around the world. For example, Huo et al [1] and Li et al [2] analyzed the mechanical properties of the cutterhead of the shield machine, and optimized the cutterhead to significantly reduce the equivalent stress and deformation of the cutterhead; Shi et al [3] analyzed the torque of cutterhead of the EPB shield machine, and found that the cutter opening and earth pressure are two important factors affecting torque of the cutter; Qi et al [4] studied the rock breaking process of the cutter of the road header, and determined the optimal knife spacing of the rock; Moeinossadat et al [5] , Zhu、Li [6] and Li et al [7] studied the surface subsidence caused by shield tunneling, and proposed effective methods for predicting surface settlement; Ooishi et al [8] developed a shield bulldozer measuring device to facilitate accurate measurement of the discharged muck; Shi et al [9][10] and Yang et al [11] analyzed the energy conservation of the shield machine system to reduce the energy loss of the shield machine; Yang et al [12][13] ,Wang et al [14][15] , Zhang et al [16] and Zhao et al [17] studied the dynamics of the shield thruster system which is helpful for the in-depth study of the dynamic characteristics of the shield thrust system;…”
Section: Introductionmentioning
confidence: 99%